ТИЛШУНОСЛИКДА СЎЗ БИРИКМАСИНИНГ МОҲИЯТИ ҲАҚИДАГИ МУНОЗАРАЛАР - Бобоева, М.Х. (SCIENCE and SOCIETY, 2022)
The article reflects on the history of the formation of the theory of word combinations and the problems awaiting solution in the field of researching general theoretical problems of word combinations. In the middle of the last century, efforts to study the system of word combinations intensified, and a number of researches were carried out to describe the morphosyntactic, syntagmatic, semantic factors that make up words of this system unit, and to distinguish and classify word combinations from other linguistic units. The conclusions reached as a result of the research gave impetus to the theory of the word combination system.
Keywords: word-combination (phase); syntax; system; linguistics; linguistic unit